2016
DOI: 10.1523/jneurosci.2199-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Newly Formed Endothelial Cells Regulate Myeloid Cell Activity Following Spinal Cord Injury via Expression of CD200 Ligand

Abstract: This manuscript focuses on a novel mechanism of inflammation-regulation following spinal cord injury (SCI), orchestrated by CD200-ligand (CD200L) expressed by newly formed endothelial cells within the lesion site. Our study reveals that, in homeostasis, CD200L is expressed by endothelial cells of the mouse blood-cerebrospinal fluid barrier and of the blood-leptomeningeal barrier, but not by endothelial cells of the blood-spinal cord barrier. Following SCI, newly formed endothelial cells located within the epic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 82 publications
1
10
0
Order By: Relevance
“…We found these meningeal TLS-like ectopic structures during the late phase of response to acute injury, when apparently moderate levels of unresolved inflammation persist within the spinal cord parenchyma ( Shechter et al, 2009 ; Cohen et al, 2014 , 2017 ; Raposo et al, 2014 ). These meningeal structures were observed in close proximity to the site of insult within the parenchyma, harboring cells with immunological properties that differed from the lymphocytes found in the spinal cord parenchyma or in the cLN.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…We found these meningeal TLS-like ectopic structures during the late phase of response to acute injury, when apparently moderate levels of unresolved inflammation persist within the spinal cord parenchyma ( Shechter et al, 2009 ; Cohen et al, 2014 , 2017 ; Raposo et al, 2014 ). These meningeal structures were observed in close proximity to the site of insult within the parenchyma, harboring cells with immunological properties that differed from the lymphocytes found in the spinal cord parenchyma or in the cLN.…”
Section: Discussionmentioning
confidence: 75%
“…Following any deviation from homeostasis in the central nervous system (CNS), the immune response is activated to facilitate repair and to resolve the detrimental parenchymal inflammation. Despite the privileged nature of the CNS, many immunological process take place within its boundaries, both in homeostasis and under pathological conditions, with similarities to those that occur in the periphery ( Lalancette-Hebert et al, 2007 ; Liesz et al, 2009 ; Shechter et al, 2009 ; David & Kroner, 2011 ; London et al, 2011, 2013 ; Martino et al, 2011 ; Michaud et al, 2013 ; Cohen et al, 2014, 2017 ; Peruzzotti-Jametti et al, 2014 ; Raposo et al, 2014 ; Kunis et al, 2015 ; Russo & McGavern, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial cells from injured blood vessels were slow to reform blood vessels and were rarely invading the lesion site. In contrast, in mammals endothelial cells accumulate in the injury site, where they may have anti-inflammatory functions 51 . Myelinating cells bridged the lesion site, but were not abundant and only did so, when axons had already crossed the lesion site.…”
Section: Discussionmentioning
confidence: 99%
“…This effect was further shown to rely on BDNF/TrkB signaling [ 47 ], as well as inhibition of matrix metalloproteinases (MMPs) [ 173 ], which restructure extracellular matrices and damage the blood–spinal-cord barrier after SCI [ 174 , 175 ]. Interestingly, another study found that after SCI, proliferating endothelial cells located in the core of the lesion upregulate CD200, which hinders inflammation [ 176 ], while yet another study found that treadmill exercise upregulates both CD200 and its receptor after stroke in rats [ 177 ]. Thus, it is possible that the decrease in inflammatory signaling observed with exercise occurs in part by increasing the endothelial release of CD200 and increasing the expression of the CD200 receptor.…”
Section: Other Considerationsmentioning
confidence: 99%